Paeoniae Radix Rubra can enhance fatty acid β-oxidation and alleviate gut microbiota disorder in α-naphthyl isothiocyanate induced cholestatic model rats - Xu, Jing-Jing; Xu, Feng; Wang, Wei; Wang, Peng-Pu; Xian, Jing; Han, Xing; Shang, Ming-Ying; Liu, Guang-Xue; Wang, Xuan; Cai, Shao-Qing (Frontiers in Pharmacology, 2022)
Cholestasis is the most destructive pathological manifestation of liver disease and available treatments are very limited. Paeoniae Radix Rubra (PRR) is an important traditional Chinese drug used to treat cholestasis. This study combined targeted metabonomics, PCR array analysis, and 16S rRNA sequencing analysis to further clarify the mechanisms of PRR in the treatment of cholestasis. PRR conspicuously reversed the elevation of fatty acids (FFA 14:0 and other 14 fatty acids) and the decrease of organic acids (pyruvic acid and citric acid) in a cholestatic model induced by α-naphthyl isothiocyanate (ANIT). Eight elevated amino acids (L-proline, etc.) and five elevated secondary bile acids (taurohyodeoxycholic acid, etc.) in model rats were also reduced by PRR. Pathway analysis revealed that PRR significantly alleviated eight pathways (β-alanine metabolism). Furthermore, we found that PRR significantly reversed the decrease of Cpt1a, Hadha, Ppara, and Slc25a20 (four genes relevant to fatty acid β-oxidation) mRNAs caused by ANIT, and PRR conspicuously decreased nine acylcarnitines (the forms of fatty acids into mitochondria for β-oxidation) that increased in model rats. These results indicate that PRR could enhance fatty acid β-oxidation, which may be the way for PRR to reduce the levels of 15 fatty acids in the serum of model rats. 16S rRNA sequencing analysis revealed that PRR alleviated gut microbiota disorders in model rats, including upregulating four genera (Coprococcus, Lactobacillus, etc.) and downregulating four genera (Bacteroides, Escherichia, etc.). As the relative abundance of these eight genera was significantly correlated with the levels of the five secondary bile acids (deoxycholic acid, taurolithocholic acid, etc.) reduced by PRR, and Bacteroides and Escherichia were reported to promote the production of secondary bile acid, we inferred that the downregulation of PRR on five secondary bile acids in model rats was inseparable from gut microbiota. Thus, the gut microbiota also might be a potential pharmacological target for the anticholestatic activity of PRR. In conclusion, we consider that the mechanisms of PRR in treating cholestasis include enhancing fatty acid β-oxidation and alleviating gut microbiota disorders.